Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Drug-drug cocrystals of anticancer drugs erlotinib-furosemide and gefitinib-mefenamic acid for alternative multi-drug treatment - George, Christy P.; Thorat, Shridhar H.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (Crystengcomm, 2020)
Drug-drug cocrystals of anticancer drugs erlotinib and gefitinib with furosemide and mefenamic acid, respectively, have been synthesized. The 1:1 erlotinib-furosemide cocrystal crystallizes in the monoclinic centrosymmetric P2(1)/n space group containing one molecule of each component in the asymmetric unit. In contrast the 1:1 gefitinib-mefenamic acid cocrystal hydrate belongs to the monoclinic centrosymmetric P2(1)/c space group comprising one molecule of both drugs along with one water molecule in the asymmetric unit. The solubility and dissolution rate study revealed higher solubility for BCS class II drugs, furosemide, and mefenamic acid, while the solubility and dissolution rate of erlotinib showed a significant reduction in the cocrystal salt. Conversely, the solubility of gefitinib didn't reveal a substantial decrease; however, the dissolution rate has been reduced in the cocrystal hydrate. Further, an attempt has been made to correlate the crystal structures of the erlotinib-furosemide and gefitinib-mefenamic acid cocrystals with their solubilities and dissolution rate.